Perilaku Bullying Terhadap Kepercayaan Diri Siswa - Tadhawwara Puji Astuti; Haning Tri Widiastuti (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
Bullying behavior is a problem in this research. With cases of bullying behavior carried out by students against their own friends, such as physical, verbal, cyberbullying and relational bullying. This research was conducted with the aim of finding out whether there is an influence of bullying behavior on students' self-confidence at SMAN 3 Depok. This research uses associative quantitative which looks at the influence between variables X and Y. The sampling technique used was simple random sampling, totaling 260 people. The research results showed